Joop van der Horst, 2016: Propast standardnoga jezika. Mijena u jezičnoj kulturi Zapadne Europe: Zagreb: Srednja Europa. 258 str. - Puškar, Krunoslav (Slavia Centralis, 2020)
The author of the article presents the monograph Propast standardnoga jezika. Mijena u jezičnoj kulturi Zapadne Europe (The Destruction of the Standard Language. A change in the linguistic culture of Western Europe; with the original title Het einde van de standaardtaal. Een wisseling van Europese taalcultuur), which was translated into Croatian in 2016.